Praktik Upah Jasa Penggilingan Padi Keliling Perspektif Hukum Islam - Rafica Oktaviani; Niswatul Hidayati (Fakultas Syariah Institut Agama Islam Negeri Ponorogo, 2021)
This research departs from the community's problem of taking rice bran as an additional wage for mobile rice milling services. The purpose of this study focuses on the phenomenon of wages (Ijarah) for mobile rice mill services, which is then analyzed based on the perspective of Islamic law. The type of research used is field research using qualitative research methods and data collection techniques through interviews. In this study, it was found that the wages of the mobile rice milling contract in Gegeran Sukorejo Ponorogo Village were not entirely following Islamic law because the determination of wages was only carried out by one party and taking additional wages in the form of rice bran without any openness and willingness from the farmers, thus harming one of the farmers. Parties, namely farmers or consumers. Regarding the Ijarah agreement, the mobile rice mill service in Gegeran Sukorejo Village, Ponorogo, is not entirely following Islamic law because the transaction does not fulfil the principles in the contract, especially the principle of ibahah, the principle of trust (honesty), fairness and balance of achievements. Although in the transaction between the two, there is a valid qabul ijāb.